Activated monocytes resist elimination by retinal pigment epithelium and downregulate their OTX2 expression via TNF‐α. Issue 1 (22nd September 2016) - Mathis, Thibaud; Housset, Michael; Eandi, Chiara; Beguier, Fanny; Touhami, Sara; Reichman, Sacha; Augustin, Sebastien; Gondouin, Pauline; Sahel, José‐Alain; Kodjikian, Laurent; Goureau, Olivier; Guillonneau, Xavier; et al.
Summary: Orthodenticle homeobox 2 (OTX2) controls essential, homeostatic retinal pigment epithelial (RPE) genes in the adult. Using cocultures of human CD14 + blood monocytes (Mos) and primary porcine RPE cells and a fully humanized system using human‐induced pluripotent stem cell‐derived RPE cells, we show that activated Mos markedly inhibit RPE OTX2 expression and resist elimination in contact with the immunosuppressive RPE. Mechanistically, we demonstrate that TNF‐α, secreted from activated Mos, mediates the downregulation of OTX2 and essential RPE genes of the visual cycle among others. Our data show how subretinal, chronic inflammation and in particular TNF‐α can affect RPE function, which might contribute to the visual dysfunctions in diseases such as age‐related macular degeneration (AMD) where subretinal macrophages are observed. Our findings provide important mechanistic insights into the regulation of OTX2 under inflammatory conditions. Therapeutic restoration of OTX2 expression might help revive RPE and visual function in retinal diseases such as AMD.